Tokyo ghoul [videorecording (DVD)] - Hagiwara, Kentar; Kubota, Masataka, 1988-; Shimizu, Fumika; Suzuki, Nobuyuki (Actor); Ishida, Sui (FUNimation, 2018)
Having survived an attack by a ghoul, a college student discovers that he has turned into a part-ghoul himself and now needs to learn to live with his new identity.